The treaties of Karlowitz – research problems - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2003)
The Treaties of Karlowitz, signed in 1699, ended the long-standing war between the Ottoman Empire and the coalition of the Holy League (Austria, the Polish-Lithuanian Commonwealth, Venice, and Russia). Despite their crucial significance for the history of Central and Eastern Europe, these treaties have not yet received a modern, comprehensive scholarly study. The article seeks to outline the key research problems related to this topic. The aim of the study is to identify the gaps and controversies in existing historiography concerning the Karlowitz Treaties and to analyze the reasons for the absence of an integrated scholarly account. The author presents the political circumstances of the ongoing war, the interests of each coalition member, and the difficulties encountered during the peace negotiations. Special attention is given to the divergent goals of the Emperor, Poland, Venice, and Russia, as well as to the role of Anglo-Dutch mediation. The author highlights a substantial body of untapped archival materials, particularly in the archives of Vienna, Warsaw, Venice, and potentially in Russian and Turkish collections. She points to the urgent need for a critical edition of the treaty texts, which currently exhibit numerous discrepancies in published versions.